Feasibility of fox-nut ranching in beels of Assam a case study - Dutta, P K; Baruah, U K; Bhagowati, A K (Indian Journal of Fisheries, 2011)
Euryale ferox is a common aquatic weed of the beels of Assam. Of late, it hasbecome a cash crop for the people who depend on beels for their livelihood. A casestudy on foxnut (Euryale ferox) ranching was conducted at the Batamari beel ofAssam. The study revealed fox-nut productivity @ 19,047 Kg/ha/yr. in the Batamaribeel. Costs and benefits analysis for 5 year project showed that total cost requirementfor fox-nut ranching in an area of 0.21 ha was Rs. 51,000.00 andinvestment’s internal rate of return (IRR) was 119.39%. Net present value (NPV)was calculated to be Rs. 1,26,651.15. It indicates the feasibility of commercialfarming of fox-nut in beels